Effects of a step-by-step inpatient rehabilitation program on self-care ability and quality of life in patients with acute cerebral infarction following intravascular stent implantation: a prospective cohort study - Wei, Chen; Xi, Nannan; Tang, Jieqiong; Chu, Qiangqiang; Bi, Qingquan (Frontiers in Neurology, 2024)
Objective This study aims to evaluate the influence of a step-by-step inpatient rehabilitation program (SIRP) on the self-care capability and quality of life of patients who have undergone intravascular stent implantation to treat large vessel occlusion during acute cerebral infarction (ACI). Methods This study included a cohort of 90 patients with ACI who received intravascular stent implantations at a tertiary hospital in the Third Affiliated Hospital of Anhui Medical University from January 2020 to February 2024. The patients were followed up for at least 3 months. Cohort grouping was based on the type of nursing care each patient received. The observation group participated in SIRP along with receiving routine nursing care, whereas the control group received only routine nursing care. Key outcome measures included the Barthel index, the National Institute of Health Stroke Scale (NIHSS) score, the incidence of complications, length of hospital stay, and 36-item short-form survey (SF-36) scores. These parameters were compared between the two groups. Results At the time of admission, there were no significant differences in demographic data, NIHSS score, Barthel index, or SF-36 scores between the observation and control groups (all p > 0.05). However, at 3 months postoperatively, the observation group showed significant improvements, with higher average scores in the Barthel index (62.49 ± 7.32 vs. 53.16 ± 4.37, p < 0.001) and SF-36 scores (502.33 ± 14.28 vs. 417.64 ± 9.65, p < 0.001). Additionally, this group had significantly lower NIHSS scores (3.38 ± 1.19 vs. 10.24 ± 2.10, p < 0.001), fewer complications (3 vs. 15, p = 0.002), and shorter hospital stays (12.40 ± 1.68 vs. 15.56 ± 1.87, p < 0.001). Conclusion Implementing SIRP notably enhanced self-care capabilities and overall quality of life, while also reducing complication rates and the length of hospital stays for patients with ACI who underwent intravascular stent implantation. This underscores the potential benefits of incorporating structured rehabilitation programs in the treatment and recovery processes of such patients.